Primary adrenal insufficiency in adult population: a Portuguese multicentre study by the Adrenal Tumours Study Group - Ferreira, L (2017)
INTRODUCTION: Primary adrenal insufficiency (PAI) is a rare but severe and potentially life-threatening condition. No previous studies have characterized Portuguese patients with PAI. AIMS: To characterize the clinical presentation, diagnostic workup, treatment and follow-up of Portuguese patients with confirmed PAI. METHODS: This multicentre retrospective study examined PAI patients in 12 Portuguese hospitals. RESULTS: We investigated 278 patients with PAI (55.8% were females), with a mean age of 33.6±19.3 years at diagnosis. The most frequent presenting clinical features were asthenia (60.1%), mucocutaneous hyperpigmentation (55.0%) and weight loss (43.2%); 29.1% of the patients presented with adrenal crisis. Diagnosis was established by high plasma ACTH and low serum cortisol in most patients (43.9%). The most common etiology of PAI was autoimmune adrenalitis (61.0%). There were 38 idiopathic cases. Autoimmune comorbidities were found in 70% of the patients, the most frequent being autoimmune thyroiditis (60.7%) and type 1 diabetes mellitus (17.3%). Seventy-nine percent were treated with hydrocortisone (mean dose 26.3±8.3 mg/day) mostly in three (57.5%) or two (37.4%) daily doses. The remaining patients were treated with prednisolone (10.1%), dexamethasone (6.2%) and methylprednisolone (0.7%); 66.2% were also on fludrocortisone (median dose of 100 g/day). Since diagnosis, 33.5% of patients were hospitalized for disease decompensation. In the last appointment, 17.2% of patients had complaints (7.6% asthenia and 6.5% depression) and 9.7% had electrolyte disturbances. CONCLUSION: This is the first multicentre Portuguese study regarding PAI. The results emphasize the need for standardization in diagnostic tests and aetiological investigation and provide a framework for improving treatment.